The Use of Educative Game Tools (Meronce Lego) to Support the Motor Development of Preschool Children at TA Pesan Ibu - Wahidyanti Rahayu Hastutiningtyas; Irawan Setyabudi; Neni Maemunah (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Pre-school period is the stage of development of children aged 3-6 years where at this age children will learn to interact with other people. Educational Game Tools (APE) are all forms of games designed to provide educational experiences or learning experiences to the players. Message Mother Kindergarten is one of the places to stimulate the development of preschool-aged children, however APE in the form of Meronce Lego available at schools is still not optimal where the availability of educational game tools itself does not match the number of children so there is a need for additions and understanding to improve children's development and Children feel bored with monotonous games. The solution that will be provided is to provide training in the Selection of Educational Game Tools (APE), Assistance explaining the uses and functions of Educational Game Tools (APE) and Promotion of Educational Game Tools (APE). The output target to be produced is in the form of activity videos which are published via YouTube with the link: https://youtu.be/ZISk0JYROWE. All students can play Meronce Lego happily with their friends. Thus the TA teacher, especially the TA Pesan Ibu, can introduce educational game tools such as lego meronce which is appropriate for one of the lessons in the classroom so that children don't feel bored with this type of game. Students play the lego meronce game so that it can improve children's motor development.